ANALISA LAPORAN KEUANGAN BUPDA TEJA RAHAYU DESA ADAT TEJAKULA - Putra, Gede Rama Laksana; Werastuti, Desak Nyoman Sri (Universitas Pendidikan Ganesha, 2022)
BUPDA Teja Rahayu is one of business entities belonging to the newly forme Tejakula Traditional Village. There are still many systems that need to be re-applied in the oprations of BUPDA Teja Rahayu itself. One of the systems in question is a system in financial recording of financial reports which will later serve as material for the accountability of BUPDA Teja Rahayu to the Bendesa Adat or LPD Desa Pakraman Tejakula as the superior of this business entity. Meanwhile, the records carried out by BUPDA Teja Rahayu only recorded cash receipts and disbursements, which led to several questions from the leadership of BUPDA Teja Rahayu regarding ambiguous financial records.